The recyclability and printability of electrophotographic printed paper - SÖNMEZ, SİNAN (My University, 2022)
Paper is the most successful recycled material from commercial and municipal wastes. Part of recycled paper requires deinking to meet the product requirement, such as tissue, printing grade and newspaper. The original print method plays a major role in deinking performance. The digital print methods, such as electrophotographic (or laser) print, have been rapidly adapted in the commercial printing. Paper mills need to modify their procedure to deink these types of recycled paper, which contain fine toner particles. In this study, the recyclability of electrophotographic printed paper has been evaluated extensively, or three repeats with an industrial standard. Meanwhile, recycled fiber from each repeat underwent printability analysis. Except the influence from papermaking method and pulp furnish, the strength of the recycled fiber slightly declines after each repeat because of fiber deterioration, which also affected the paper surface properties. However, the recycled fiber presented good printability on each recycling, especially on print density and fine details. It suggested that the electrophotographic substrate can tolerate a high recycled fiber content.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, KAĞIT & AHŞAP; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, PAPER & WOOD; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; electrophotographic printing system; printability; recycling; toner; COLOR; COMPONENTS; ROUGHNESS; FIBERS; PULP